Commentary on “Epigenome-wide analysis across the development span of pediatric acute lymphoblastic leukemia: backtracking to birth” - Emma Raitoharju; Saara Marttila (Molecular Cancer)
Abstract VTRNA2-1 is a polymorphically imprinted locus. The proportion of individuals with a maternally imprinted VTRNA2-1 locus is consistently approximately 75% in populations of European origin, with the remaining circa 25% having a non-methylated VTRNA2-1 locus. Recently, VTRNA2-1 hypermethylation at birth was suggested to be a precursor of paediatric acute lymphoblastic leukaemia with biomarker potential. The results presented by Ghantous et al. [1] allow for an alternative interpretation to what the authors discussed, and we argue that the observed methylation difference at birth is due to an uneven distribution of imprinted and non-methylated individuals among the cases and controls, with all individuals presenting normative physiological VTRNA2-1 methylation levels. In addition, the notable interindividual variation arising from the polymorphic imprinting in VTRNA2-1 methylation levels calls into question the validity of VTRNA2-1 methylation as a biomarker.